Medicine and Humankind since Ancient Times: Historical and Legal Aspects of Joint Development - Harust, Yurii; Kurylo, Volodimir; Kiselyova, Elena; Pavlenko, Bohdana (Journal of History Culture and Art Research, 2020)
This article highlights the historical and legal foundations of the development of medicine and humankind. Based on the analysis of the results of archaeological, anthropological studies and historical sources, we legally proved that starting with the very early stages of human development, medicine existed alongside the primitive man. While investigating the state of medicine in ancient Egypt, we came to the conclusion that treatment not only helped people, but sometimes, on the contrary, greatly damaged the health of patients. For example, many recipes included the obligatory use of manure, which contains products of fermentation and mold, which is very dangerous to the body and health. However, despite these negative results, we can argue that medical practice in ancient Egypt was well developed. The The studies of this period made it possible to conclude that medicine develops in an inextricable connection with human development, and the obtained medical knowledge is used by society for its well-being. The study of the development of medicine and humanity in Ancient India gives grounds for arguing that due to advanced medical education. Society has come to the conclusion that medicine is an integral part of human life and a guarantee of its development and continuation. It was during this period that humankind switched to a new stage of healthcare when the state control of medicine emerges. It was in India where state institutions began to consider the medical sector as one of the main tools for guaranteeing the well-being of citizens. And in ancient China, medicine gained state support and became the foundation of the society’s development at the one level with religion. The results obtained in the course of our study are based on historical facts, they prove that medicine arose with the appearance of human and subsequently existed and developed along with human development.